Urban growth, social-spatial inequalities and housing policy: A case study of Cordoba - Marengo, Maria Cecilia (2020)
Numerous studies point out as a new feature of the process of socio-territorial transformations in the new century, the intensification of inequalities and the increasing difficulty in accessing affordable housing in the cities. In Cordoba Argentina, urban form is characterized by low densities, discontinuous expansion, increased segregation and urban fragmentation. The paradox is that even in a context of economic growth (during the first decade of the 21st century) the housing deficit and urban informality enlarged.The objective of the research is to determine the way in which housing policy has influenced the production of new territories. The methodology seeks to integrate quantitative and qualitative approaches. The results allow us to recognize processes of urban fragmentation, as well as the conditions derived from the peripheral location of housing policy. In this way, we seek in this study to advance in the notion of more inclusive residential environments.